Sharing Cancer Survivorship Care between Oncology and Primary Care Providers: A Qualitative Study of Health Care Professionals’ Experiences - Lisy, Karolina (J Clin Med, 2020)
Survivorship care that is shared between oncology and primary care providers may be a suitable model to effectively and efficiently care for the growing survivor population, however recommendations supporting implementation are lacking. This qualitative study aimed to explore health care professionals’ (HCPs) perceived facilitators and barriers to the implementation, delivery and sustainability of shared survivorship care. Data were collected via semi-structured focus groups and analysed by inductive thematic analysis. Results identified four overarching themes: (1) considerations for HCPs; (2) considerations regarding patients; (3) considerations for planning and process; and (4) policy implications. For HCPs, subthemes included general practitioner (GP, primary care physician) knowledge and need for further training, having clear protocols for follow-up, and direct communication channels between providers. Patient considerations included identifying patients suitable for shared care, discussing shared care with patients early in their cancer journey, and patients’ relationships with their GPs. Regarding process, subthemes included rapid referral pathways back to hospital, care coordination, and ongoing data collection to inform refinement of a dynamic model. Finally, policy implications included development of policy to support a consistent shared care model, and reliable and sustainable funding mechanisms. Based on study findings, a set of recommendations for practice and policy were developed.